A case study of the greater Mekong subregion : bases for strategic alliances. - Ho, Hsueh Ling. (2008)
The case study is concerned with the factors that are important as a foundation for tourism marketing alliance formation and operation within the context of the Greater Mekong Subregion (GMS).